Kekuatan Keterangan Saksi Anak sebagai Korban dalam Pembuktian Jarimah Pemerkosaan Anak - Nabila Salsta Luthfiyyah; Abdul Salam (Al-Azhar Islamic Law Review, 2023)
Witness testimony as evidence in the evidentiary process is one of the important indicators that can determine that a crime has actually occurred and the accused is the perpetrator. Children as victims in the crime of rape against children here include witnesses who see and experience the incident themselves. The goal to be achieved in this research is to find out how far the strength of the testimony of child witnesses as victims in evidence at trial. This research itself is included in the type of normative research, namely research that emphasizes regulations related to the object being analyzed. The method used is descriptive analytical method, namely a method that describes research critically through qualitative analysis. The data used in this study are secondary data obtained from Decision Number 7/JN/2022/MS.Bna as well as review literature in the form of both secondary data which in writing are taken from various journals, books or articles on the internet related to testimony of child witnesses as victims in proving the crime of child rape. Based on the results of the research, the statements of witnesses of children under oath as victims of the criminal act of rape against children in the Aceh Qanun and the Criminal Procedure Code have similarities. The child witness's statement is not used as legal evidence, but if the child witness's statement is in accordance with the witness who has been sworn in, then it can be used as a guide or additional legal evidence